(untitled) (Bioagro, 2020)
Soil quality is considered a measure of the sustainability of land use and agricultural management practices. This quality can be determined by monitoring different types of physical, chemical and biological soil indicators. The objective of the present study was to evaluate the effect of the implementation of different agricultural management in four representative production systems (PS) such as polyculture, organic coffee cultivation, crop of Sechium edule, and pasture at rest) at the municipality of Cachipay in Cundinamarca, Colombia. Two sampling events were carried out in June and September 2016, in which two sampling areas were selected for each PS. Within each area, two quadrants (2.5 x 2.5 m) were established from which two composite samples (25 subsamples each) of soil (0-15 cm) were taken. The results show that the polyculture and the organic coffee crop positively impact the physical state of the soil (penetration resistance, mean weighted diameter, stability index, and aggregation states), which seems to generate a better environment for edaphic microorganisms, reflected in a higher density of total heterotrophs and higher catalase enzymatic activity. It showed that implementation of different agricultural management practices in the PS generates modifications in the soil properties, which can alter the soil processes and their functioning.